I'll walk alone eaudiobook - Higgins Clark, Mary (Alvirah and Willy., 2014)
Number one best-selling author Mary Higgins Clark has sold over 100 million copies of her books in the U.S. alone. Known worldwide as the Queen of Suspense and an oft-imitated living legend among mystery writers, Clark delivers suspense novels as only she can. A tautly paced page-turner, I'll Walk Alone will be eagerly devoured by Clark's many fans. "Mary Higgins Clark is a master plotter, seeding with crimes, clues, and psychopathic quirks that pay off."—New York Times Book Review